Perbandingan Efektivitas Seduhan Daun Pepaya (Carica papaya Linn) Dengan Temephos 1% Sebagai Biolarvasida Nyamuk Culex sp - Benaya Yamin Onesiforus; Elisa Rinihapsari; Timotius Ando Yordan; Titania Constance (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
Mosquitoes are group of insect with an impact to human health. Female mosquito has a habit of blood feding for maturing their eggs after mating. Mosquito-borne diseases might be transmitted during their blood sucking activity. Filariasis is a mosquito-borne diseases which has plagued Indonesia since long time and can still be found in the east part of Indonesia. Therefore mosquitoe population control had been an important issue in Indonesia.. Larvacides application is one of the most effective method to control mosquitoes spread by cutting their life cycle. Larvicides can be either synthetic or natural. One of the natural materials that can be used as larvicide is papaya leaves. This study objective was to compare the effectiveness of papaya leave and temephos 1% in killing mosquito larvae. This type of research is experimental with purposive sampling technique. Data were analyzed using Kruskal Wallis statistical test and Mann Whitney posthoc test. The results indicate a significant difference (p<0.05) in effectiveness between temephos and pineapple peel steeping concentration with temephos 1% has better the effectiveness as mosquitoes larvicide than pineapple peel steeping..